Metastable Solubilities and Thermodynamic Properties of SrSO4 Scale at 278.2 to 323.2 K - Wei, Cui; Sang, Shi-Hua; Hu, Juan-Xin; Li, Da-Wei; Zhong, Si-Yao; Huang, Wang-Yin (Asian Journal of Chemistry, 2015)
In this paper, the isothermal evaporation method was used to determine the metastable solubilities of strontium sulfate (SrSO4) at (278.2, 283.2, 303.2 and 323.2) K. During the evaporation progress, the concentrations of SrSO4 were measured at a period time and a set of the results were fitted to empirical equations of evaporating times. The metastable solubilities were determined by the maximum concentration and the metastable region of SrSO4 at 278.2 to 323.2 K was determined. By using simplified Pitzer equations and metastable solubilities at the given temperatures, the thermodynamic properties of SrSO4 (g±, F, GE) were calculated and all the calculated results were compared with the stable values calculated by the literature solubilities in this work. Then the thermodynamic ion product (Qsp) of SrSO4 were calculated and compared with the thermodynamic solubility product (Ksp) of SrSO4 at different temperatures.